Controllable beam reshaping by mixing square-shaped and hexagonal optical vortex lattices - Stoyanov, Lyubomir; Maleshkov, G.; Zhekova, Maya; Stefanov; Paulus, Gerhard G.; Dreischuh, Alexander (Scientific Reports, 2019)
In the present work we show experimentally and by numerical calculations a substantial far-field beam reshaping by mixing square-shaped and hexagonal optical vortex (OV) lattices composed of vortices with alternatively changing topological charges. We show that the small-scale structure of the observed pattern results from the OV lattice with the larger array node spacing, whereas the large-scale structure stems from the OV lattice with the smaller array node spacing. In addition, we demonstrate that it is possible to host an OV, a one-dimensional, or a quasi-two-dimensional singular beam in each of the bright beams of the generated focal patterns. The detailed experimental data at different square-to-hexagonal vortex array node spacings shows that this quantity could be used as a control parameter for generating the desired focused structure. The experimental data are in excellent agreement with the numerical simulations.
CRIS-Team Scopus Importer:2023-04-20